Juvenile Detention and Correctional Facility Census, 1975 ([Verlag nicht ermittelbar], 1984)
The 1975 census includes juvenile detention and correctional facilities that were operated by state or local governments in November, 1975, and had been in operation at least a month prior to June 30, 1975. There is one record for each juvenile detention facility that had a population of at least 50 percent juveniles. Each record is classified into one of six categories: detention centers or shelters, reception or diagnostic centers, training schools, ranches, forestry camps and farms, and halfway houses and group homes. Data include state, county, and city identification, level of government responsible for the facility, type of agency, agency identification, resident population by sex, age range, detention status, and offense, admissions and departures of population, average length of stay, staffing and expenditures, age and capacity of the facility, and programs and services available.